2011
DOI: 10.1242/jcs.071928
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing dynamic cytoplasmic forces with a compliance-matched FRET sensor

Abstract: SummaryMechanical forces are ubiquitous modulators of cell activity but little is known about the mechanical stresses in the cell. Genetically encoded FRET-based force sensors now allow the measurement of local stress in specific host proteins in vivo in real time. For a minimally invasive probe, we designed one with a mechanical compliance matching that of many common cytoskeleton proteins. sstFRET is a cassette composed of Venus and Cerulean linked by a spectrin repeat. The stress sensitivity of the probe wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
183
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(185 citation statements)
references
References 26 publications
2
183
0
Order By: Relevance
“…This changed with the development of genetically coded FRET-based force probes (2, 10). To calibrate the intrinsic force sensitivity of these probes, we used DNA springs to stretch the probes in solution and showed that the probes responded clearly to forces in the range of 10 pN (7,10,11). We have calibrated the strain sensitivity of the earlier linear linked probes and showed FRET to be linear as predicted (2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This changed with the development of genetically coded FRET-based force probes (2, 10). To calibrate the intrinsic force sensitivity of these probes, we used DNA springs to stretch the probes in solution and showed that the probes responded clearly to forces in the range of 10 pN (7,10,11). We have calibrated the strain sensitivity of the earlier linear linked probes and showed FRET to be linear as predicted (2).…”
Section: Discussionmentioning
confidence: 99%
“…The angular probe uses the dipole orientation dependence of FRET, allowing FRET efficiencies, in principle, from 0% to 100% (2,8,11). The dimeric structure of cpstFRET mimics the dimer subunit structure of many multimeric cytoskeleton proteins such as actin and tubulin ( Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells withstand mechanical loading through support from cytoskeleton, a heterogeneous, anisotropic collection of dynamically cross-linked structural proteins. [41][42][43][44][45] The deformation of a cell depends on the intrinsic elastic deformation of fibrous cytoskeletal proteins and plastic deformation involving dynamics of reversible cross-linking and cytoskeleton reorganization. 46,47 Slow shear loading engages the plastic processes that significantly modify the local force around the Ca 2 + transducers acting like dashpots in series with the transducer.…”
Section: Discussionmentioning
confidence: 99%